The society human immunodeficiency virus health literacy scale: the development and psychometric assessment - Wilandika, Angga; Yusuf, Ah.; Kurniawati, Ninuk Dian Indah; Sari, Diah Nur Indah (International Journal of Public Health Science (IJPHS), 2024)
Society human immunodeficiency virus (HIV) related health literacy is an essential behavioural skill that contributes to understanding the disease and responding to people living with HIV. Measuring HIV health literacy in the community requires reliable tools to produce an objective health literacy index. This study aimed to design and examined the society HIV health literacy scale's (SHIVAL) psychometric properties. A cross sectional study was conducted on 381 people without HIV. Sample recruitment used convenience sampling. Instrument development and psychometric analysis include item pool construction and content validity examination, consistency reliability test, and exploratory and confirmatory factor analysis. A standardized four factor model fits the HIV health literacy measure well. This scale has 15 items with good Cronbach's Alpha reliability index and content validity index. The final SHIVAL Scale has been determined reliable and appropriate for measuring health literacy related to HIV. Nurses or healthcare professionals can use this scale to predict an individual's HIV health literacy, thereby influencing the social intervention of HIV disease and enabling effective community health literacy strategies.